Analysis of Batik Solo Trans Service Area to Schools and Settlements in Surakarta City - Syaharini, Jay She; Wijaya, Arwan Putra; Prasetyo, Yudo (Universitas Islam Sultan Agung Semarang, 2024)
Surakarta city has public transportation called Batik Solo Trans (BST). Batik Solo Trans has a system of going up or down at certain locations called bus stops. However, the problems that arise are in the form of service and availability of BST stops for schools and settlements. It is necessary to analyze the BST bus stop service areas for schools and settlements in Surakarta City. This research is carry out using the Network Analysis method with a distance of 400 meters to determine the service coverage area from the Batik Solo Trans bus stop to schools and residential areas in Surakarta City. The results of the service area processing show that the service area at the existing BST bus stop can reach 126 elementary schools, 47 middle schools and 21 high schools in the city of Surakarta. Meanwhile, in settlements there are 43 urban villages that can already be served with existing BST bus stops. Then a recommendation is made for the potential of the BST bus stop so that it can serve schools and settlements in Surakarta city. The recommended BST bus stops are 11 stops spread across several locations.